Corporate governance and earnings management: A quantile regression approach - Feng, Zhi‐Yuan; Huang, Hua‐Wei (International journal of finance and economics, 2021)
The effects of corporate governance (CG) on earnings management (EM) have been debated for many years. Thus, this paper explores this issue in a novel way that utilizes a quantile regression to revisit the association between CG mechanisms and EM. We find that a non‐uniform relation between CG mechanisms and EM for non‐financial U.S. firms does exist from 2007 to 2015. Specifically, the empirical evidence documents that CG mechanisms can effectively constrain earning manipulation among firms with higher discretionary accruals (High EM). However, this effect becomes insignificant for firms with medium and low levels of discretionary accruals (Low EM). The quantile‐varying results provide further support for the theoretical viewpoint that the CG mechanism can serve as an effective tool for supervising management in the financial accounting process but only in the case of firms with aggressive EM behaviour.